Carbon Isotopic Signature and Organic Matter Composition of Cenomanian High-Latitude Paleosols of Southern Patagonia - Varela, Augusto Nicolás (2021)
The Cenomanian Mata Amarilla Formation (MAF) in southern Patagonia (~55° S paleolatitude, Austral-Magallanes Basin, Argentina) is composed mainly of stacked fluvial deposits with intercalated paleosols, which document Cenomanian environments at high-paleolatitudes in the Southern Hemisphere. We performed a multiproxy study of the paleosols and sediments of the MAF in order to (1) understand the composition of the soil- and sediment-derived organic matter (OM), (2) apply carbon isotope stratigraphy as a tool to correlate patterns obtained from the MAF with existing marine and non-marine δ13Corg records worldwide, and (3) investigate the relationship between variations in spore-pollen assemblages of the MAF and the climatic conditions prevailing in the Cenomanian Southern Hemisphere. An integrated dataset was generated, including total organic carbon content, Rock-Eval pyrolysis data, stable isotope (δ13Corg) composition, and palynological data, combined with published paleosol-derived mean annual temperatures and mean annual precipitations. The results indicated that the OM preserved in the MAF paleosols allowed its use as a chemostratigraphic tool. The MAF δ13Corg curve showed the rather stable pattern characteristic for the Early to Late Cenomanian interval. The absence of the major positive carbon isotope excursion associated with oceanic anoxic event 2 provided an upper limit for the stratigraphic range of the MAF. The palynological data suggested the development of fern prairies during warmer and moister periods at the expense of the background gymnosperm-dominated forests. Overall, the multiproxy record provided new insights into the long-term environmental conditions during the Cenomanian in the high latitudes of the Southern Hemisphere.